The stepwise photochromic reactivity of diarylethene tuned by selective ions and fabrication of a molecular logic circuit. (July 2021) - Yang, Jufang; Zou, Qi; Chen, Xuanying; Li, Yuezheng; Zhao, Chunrui; Weng, Taoyu; Wu, Bin; Zhu, Liangliang; Wang, Daolei; Xin, Zhiling
Abstract: The tunable photochromic systems have received wide attention in the photoelectronic fields. Herein, we report a diarylethene derivative attached with 2-hydrazylbenzothiazole via Schiff base, which shows the typical photochromic properties upon alternating irradiation with UV and visible light. Remarkably, the varying binding mode and complex strength between the diarylethene and selective metal ions (Cu 2+, Ni 2+, Cr 3+, Sn 2+ and Al 3+ ) enable the methanol solution of the diarylethene to exhibit stepwise photochromic reactivity by virtue of these metal ions. The photochromic reactivity of the diarylethene could be suppressed at different levels by the formation of the complex with Cu 2+ and Ni 2+ in a 2:1 binding mode, respectively, whereas the photochromic reactivity was enhanced to varying degrees by Cr 3+, Sn 2+ and Al 3+ in a 1:1 binding mode. Based on these multiple stimuli responses, a logic circuit with six input signals and three output signals was constructed to perform complex logical operations at the single molecular level. Graphical abstract: We first reported a Schiff-based diarylethene attached with 2-hydrazylbenzothiazole, whose photochromic reactivity could be stepwise modulated by a series of metal ions, relying on the different coordination modes and strengths between the diarylethene and these metal ions. Image 1 Highlights: A strategy to the photoreactivity of diarylethene tuned by selective ions was devised. The stepwise photoreactivity was realized by the supramolecular interaction. It could be applied to perform complicated logical operations at the single molecular level.